Basics and guidelines of tourism development in Bosnia and Herzegovina until 1914 - M. Dujmović, Sonja (Historical Thought, 2024)
The work will present a succinct review of ideological and infrastructural foundations of tourism as well as the course of its development from elite tourism to indications of the first steps ta ken towards mass tourism du ring the period of AustroHungarian rule in Bosnia and Herzegovina. The author has singled out those segments which allowed the improvement of tourism – the Bosnian and Herzegovinian railway network, accommodation capa cities, the establishment and activities of the Bosnian and Herzegovinian Tourist Club, the support of sport associations and exhibitions in the service of propaganda and politics. The new character of tourism during the first decade of the twentieth century will also be analysed.